One step oral glucose challenge test as screening and diagnostic test for Gestational Diabetes Mellitus - Yadav, Manisha; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2019)
Aim: The Diabetes in Pregnancy Study Group of India (DIPSI, 2010) guidelines recommend the non-fasting 75-g oral glucose challenge test (OGCT) as a single-step screening and diagnostic test for gestational diabetes mellitus (GDM). The aim of this study was to assess the validity of DIPSI criteria by comparing with the World Health Organization (WHO) 1999 criteria of diagnosing GDM. Methods: This study was a hospital based prospective comparative study conducted among 282 pregnant women, of gestational age of 24-28 weeks attending antenatal OPD of Patan hospital. The OGCT was performed on them irrespective of fasting state and without any dietary preparation and they were again asked to come after 3 days of unrestricted carbohydrate diet in fasting state for WHO 2-hour oral glucose tolerance test (OGTT) with 75 gram of glucose load. The value of OGCT >140 mg/dl is diagnostic of GDM (DIPSI 2010). For the reliability of this test, it was compared with WHO 2-hour OGTT. Results: Among the study population, the mean age and BMI was 26.04±4.50 and 24.08±3.30 respectively. Out of 282 patients, 8 cases (2.83%) were found to have abnormal non-fasting 75-g OGCT and 4 cases (1.41%) had abnormal WHO 2-hour OGTT. Paired t test was employed to examine the difference of blood glucose level of the tests. There was statistically significant difference (p<0.001) between the tests. The Sensitivity, specificity, positive predictive value and negative predictive value of oral glucose challenge test was 25%, 97.48%, 12.5% and 98.90% respectively. The non- fasting 75-g OGCT was able to detect only 25% of the cases. Conclusions: Though the non-fasting 75-g OGCT test is cost effective and more compliant to pregnant women, the present report suggests that it cannot be used as a single step screening and diagnostic test because of its low sensitivity. However, it is an adequate alternative for screening test in resources limited areas.